Influence of the axial tooth structure on the pressure resistance of the magnetic fluid sealing device. (August 2022) - Li, Zhenggui; Wang, Menggui; Chen, Fang; Yan, Shengnan; Li, Wangxu; Cheng, Jie
Abstract: Magnetic fluid sealing is one of the most advanced applications of magnetic fluids. Presently, the research field mainly focuses on the polar teeth, leaving a gap in the structure of the shaft. To effectively achieve the improvement of the compression resistance of the magnetic fluid sealing device, an improvement of the axial structure is required. From this perspective, this study presents a novel shaft axis gear structure for the establishment of a magnetic fluid static seal compression capacity for this model. The shaft is studied through the simulation analysis of the tooth height, the width and eccentric distance was investigated for the influence of the compression capacity. An experimental device was then used to validate the results and confirm the validity of the findings. Highlights: This study presents a novel shaft axis gear structure for the establishment of a magnetic liquid static seal compression capacity for this model. The shaft is studied through the simulation analysis of the tooth height, the width and eccentric distance was investigated for the influence of the compression capacity. An experimental device was confirm the validity of the findings.